A Review of Requirements and Approaches for Realistic Visual Perception in Virtual Reality - Gerschütz, Benjamin; Fechter, Marius; Schleich, Benjamin; Wartzack, Sandro (Proceedings of the 22nd International Conference on Engineering Design (ICED19), 2019)
The amount of new virtual reality input and output devices being developed is enormous. Those peripherals offer novel opportunities and possibilities in the industrial context, especially in the product development process. Nevertheless, virtual reality has to face several problems, counteracting reliable use of the technology, especially in ergonomic and aesthetic assessments. In particular, the discrepancies in perception between the real world and virtual reality are of great importance. Therefore, we discuss these most important issues of current virtual reality technology and highlight approaches to solve them. First, we illustrate the use cases of VR in the product development process. In addition, we show which hardware is currently available for professional use and which issues exist with regard to visual perception and interaction. Derived from the depiction of a perfect virtual reality, we define the requirements to address visual perception and interaction. Subsequently we discuss approaches to solve the issues regarding visual perception and evaluate their suitability to enhance the use of virtual reality technology in engineering design.
Keywords: Virtual reality; Visualisation; Visual perception; Eye tracking; Conceptual design